School Management Information System as a Solution for Digitizing Administration and Student Monitoring - Aris Defiana; Yoto Yoto; Didik Nurhadi (Universitas Negeri Malang, 2025)
Abstract: The acceleration of digitization in education has driven the need for systems that can effectively and efficiently manage school administration and student monitoring. This study examines the implementation of the School Management Information System (SIMS) pro.jurnale.id as a solution for the digitalization of administration and student monitoring at SMAN 1 Boyolangu. This case study employs a qualitative approach using observation, interviews, and documentation methods to evaluate the main functions of SIMS in supporting administrative processes and monitoring student development. The results indicate that the system is most frequently used in modules such as teacher and student attendance, master data management, curriculum management, and correspondence handled by administrative staff. SIMS facilitates faster data input, increases accuracy, simplifies report generation, and significantly reduces paper usage. Student monitoring has also become more effective through features like real-time attendance, daily assessments, violation records, and parent communication facilitated through homeroom teachers and guidance counselors as intermediaries. However, the study identifies several challenges, including user adaptation difficulties to new technology, network infrastructure limitations, and features that are not yet fully optimized. The researchers recommend enhanced training for teachers and staff, the development of more comprehensive features, and intensive socialization to increase parental engagement in using the system. This study provides important insights into the benefits and obstacles of digitalizing school management, serving as a foundation for developing better educational information systems in the future. Keyword: Digital School Administration, School Management Information System, Student Monitoring, Integrated School Management, Educational Case Study.